(untitled) - Kastan, David Scott (Cambridge, U.K., 2001)
This book is a authoritative account of Shakespeare's plays as they were transformed from scripts to be performed into books to be read, and eventually from popular entertainment into the centerpieces of the English literary canon. Kastan examines the motives and activities of Shakespeare's first publishers; the curious eighteenth-century schizophrenia that saw Shakespeare radically modified on stage at the very moment that scholars were working to establish and restore the "genuine" texts, and the exhilarating possibilities of electronic media for presenting Shakespeare now to new generations of readers. This is an important contribution to Shakespearean textual scholarship, to the history of the early English book trade, and to the theory of drama itself.
Keywords: Drama,Kịch,Drama,Kịch; History,Publishing,Lịch sử,Biên đạo,Editing,History,Xuất bản; Great Britain